Raising the bar (7). Issue 1 (2nd January 2018) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Corrado, Luisa; Doran, Justin; Fingleton, Bernard; Fuerst, Franz; Garretsen, Harry; Igliori, Danilo; Gallo, Julie Le; McCann, Philip; et al.
ABSTRACT: This editorial summarises the papers published in issue 13.1 so as to raise the bar in applied spatial economic research and highlight new trends. The first paper adopts a scale neutral approach to investigate the spatial mechanisms that cause regional innovation and growth. The second paper claims that population-weighting when calculating indices of regional inequality might lead to inconsistent outcomes. The third paper estimates the effect of distance between family residence and higher education institution on a student's academic performance, thereby accounting for endogenous regressors. The fourth paper shows an inverted U-shaped relationship between economic development at region of origin and the propensity to migrate using a multilevel approach. The fifth paper provides spatial econometric evidence of price competition between sellers of used books on Amazon.com. The last paper estimates a hedonic housing price equation and parameterizes the spatial weight matrix to determine how far back in time buyers, sellers and realtors are looking at the housing market.